2014
DOI: 10.1155/2014/146495
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Receptor Substrate-1 (IRS-1) Gly927Arg: Correlation with Gestational Diabetes Mellitus in Saudi Women

Abstract: Pregnant women with gestational diabetes mellitus (GDM) and type 2 diabetes mellitus (T2DM) share a common pathophysiology associated with similar risk factors. Genetic variants used to determine the risk of developing T2DM might also be associated with the prevalence of GDM. The aim of the present study was to scrutinize the relationship between the G972R polymorphism of the insulin receptor substrate-1 (IRS-1) gene with GDM in the Saudi female population. This is a case-control study that monitored 500 Saudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…147545). [5][6][7][8] Another gene associated with T2DM is the CCR5 gene (accession number. 601373).…”
Section: Introductionmentioning
confidence: 99%
“…147545). [5][6][7][8] Another gene associated with T2DM is the CCR5 gene (accession number. 601373).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Transcription factor 7-like 2 rs12255372 variant is suggested to interact with adiposity to alter β-cell function in 132 Mexican-American families with GDM [31]. Homozygosity for Insulin receptor substrate-1 G972R polymorphism might indicate an increased risk for GDM in Saudi women [32]. Interestingly, many GDM associated candidate genes can express cytokines that have been implicated in the inflammatory conditions during pregnancy [33].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study revealed that the variant (rs 1801278) of the IRS-1gene is significantly associated with GDM. The previous studies (Fallucca et al, 2006 ;Alharbi et al, 2014) [23,24,25] indicate that the polymorphic allele T is considerably related with IRS-1 and may be complicated in the development of gestational diabetes. In contrast, Shaat et al,(2005) [26] suggest that did not detect any relationship between the (rs 1801278) polymorphism and gestational diabetes.…”
Section: Discussionmentioning
confidence: 99%